2011
DOI: 10.1161/circoutcomes.110.958603
|View full text |Cite
|
Sign up to set email alerts
|

Extent of and Reasons for Nonuse of Implantable Cardioverter Defibrillator Devices in Clinical Practice Among Eligible Patients With Left Ventricular Systolic Dysfunction

Abstract: On the basis of a detailed chart review, the true rate of ICD underuse may be substantially lower than previous estimates. In addition, after accounting for ICD eligibility criteria, patient sex and age disparities in ICD therapy were no longer present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 21 publications
3
37
2
2
Order By: Relevance
“…30 The present study was not designed to collect health insurance information. In general, socioeconomic factors are likely to have a significant influence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The present study was not designed to collect health insurance information. In general, socioeconomic factors are likely to have a significant influence.…”
Section: Discussionmentioning
confidence: 99%
“…23 Smaller hospital size and lack of a cardiology service have been linked to lower rates of implantation. 29,30 A survey from New Zealand revealed that various physician-related factors could influence ICD referral, including familiarity with guidelines and perceptions of costeffectiveness. 31 In the present study, we did not have access to detailed information regarding the type of physician or center primarily responsible for individual patient care.…”
mentioning
confidence: 99%
“…In addition, after accounting for ICD eligibility criteria, patient sex and age disparities in ICD therapy were no longer present. 4 Use of a Screening Tool Improves Appropriate Referral to an Electrophysiologist for Implantable Cardioverter-Defibrillators for Primary Prevention of Sudden Cardiac Death Summary: Implantable cardioverter-defibrillators (ICDs) save lives in populations with defined clinical characteristics indicative of high risk for sudden cardiac death; however, research shows that ICDs are underused. Use of a simple screening tool in a general cardiology office increases appropriate referral of patients to an electrophysiologist for consideration for ICD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…[74][75][76][77][78] Several studies suggest that this may be true. In a study of patients receiving medical care at Duke Medical Center, 542 patients who met eligibility for ICD or CRT-D were followed up after hospital discharge (2005-2007) with a diagnosis of heart failure and LVEF ≤30%.…”
Section: Applying the Guidelines To Clinical Practicementioning
confidence: 99%
“…In a study of patients receiving medical care at Duke Medical Center, 542 patients who met eligibility for ICD or CRT-D were followed up after hospital discharge (2005-2007) with a diagnosis of heart failure and LVEF ≤30%. 75 The patients were evaluated for receipt of an ICD or a CRT-D within 1 year of the index hospitalization. Although 41% of the patients who were eligible did not receive an ICD, after consideration of the reasons, the investigators determined that only 13% of the eligible patients should have received an ICD.…”
Section: Applying the Guidelines To Clinical Practicementioning
confidence: 99%